THE IMPACT OF ‘SELFIE’ PHENOMENON AMONG THE MILLENNIAL GENERATION - Nur, Iffatin; Muttaqin, Muhammad Ngizzul (State Islamic University North Sumatra, 2020)
Abstract: The phenomenon of selfie among the millennial generation has become a very common thing to do. In the study of contemporary Islamic law, the approach of maqâshid syarî‘ah that seeks to gain mashlahât (benefits) and avoids mafsadât (harms) in human life may be used as a special consideration for dealing with the said phenomenon. This literature-based study was aimed to uncover the said phenomenon by reviewing it using mashlahât and mafsadât approaches. The results of the study indicate that the said approaches have urgency as a means of control against the selfie phenomenon practiced by the current millennial generation. Selfie should only be done if it brings benefits and goodness (mashlahât), otherwise, it must be avoided.Keywords: selfie, millennial generation, Islamic law, mashlahât, mafsadât